O Design de Interiores na reabilitação do centro histórico de Castelo Branco - Furtado, Teresa Margarida de Jesus (2016)
This document represents the conclusion of the Interior Design Master, attended at the Applied Arts School from the Polytechnic Institute of Castelo Branco, during the years 2012 to 2015. Here we show all developed work in the internship at the “Castelo Branco and Devesa Historic centerRehabilitation Office”, with focus on rehabilitation of interiors from old buildings. The project development gave special care to the building surroundings, history and heritage values. In first place a general research was made about the local environment and the historic center history and urban development, without forgetting the main thesis, recommendations and guidelines about renovations in old buildings with heritage value. After that, a rigorous survey about the building took place, with data about dimensions, pictures, materials and techniques.Taking the theoretical chapter like an example, we made an Hostel program based on a philosophy that promotes respect to the heritage and ensures its disclosure, using it as a way to extending its existence and making it known by locals and tourists. At the end, the main goal is to help in the historic center touristic promotion, using the guests as a mean to achieve it